'You're disabled, why did you have sex in the first place?' An intersectional analysis of experiences of disabled women with regard to their sexual and reproductive health and rights in Gujarat State, India - Laura Dean; Rachel Tolhurst; Renu Khanna; Kate Jehan (Taylor & Francis Group, 2017)
​Background: Globally, disabled people have significant unmet needs in relation to sexual and reproductive health (SRH). Disabled women in India face multiple discrimination: social exclusion, lack of autonomy with regard to their SRH, vulnerability to violence, and lack of access to SRH care. While they may face shared challenges, an intersectional perspective suggests that considering disabled women as a uniform and 'vulnerable' group is likely to mask multiple differences in their lived experiences. Objective: To explore commonality and heterogeneity in the experiences of disabled women in relation to their SRH needs and rights in Gujarat State, India. Methods: We conducted 22 in-depth qualitative interviews with women between the ages of 18 and 49 with any form of self-identified disability. Intersectionality was used as a lens for analysis and in sampling. Results: Findings explore the experiences of disabled women in a number of different spheres related to decision making and SRH service use. Conclusions: Recognising heterogeneity is critical to inform rights-based approaches to promote SRH and rights for all disabled women. This suggests a need to encourage strategic alliances between social movements for gender equity and SRH and disability rights, in which common interests and agendas can be pursued whilst recognising and respecting differences.